1981
DOI: 10.3171/jns.1981.55.4.0604
|View full text |Cite
|
Sign up to set email alerts
|

Chiari I “malformation”—an acquired disorder?

Abstract: Caudal herniation of the hindbrain, indistinguishable from the Chiari I deformity, may occur after the establishment of spinal subarachnoid shunts and become symptomatic years after the procedure. Examples are presented and others are cited from the literature. It is proposed that the force responsible for the displacement is the difference in pressure between the cranial and spinal compartments. On the basis of these observations and other considerations as well, a similar process, disproportionate absorption… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0
1

Year Published

1992
1992
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(58 citation statements)
references
References 21 publications
2
55
0
1
Order By: Relevance
“…However, this pressure theory has not been proven in cases of syringes associated with a Chiari I malformation and, when taken with the observation of cerebellar tonsillar descent after lumboperitoneal shunting [20, 69, 70, 71, 72, 73, 74], cannot be recommended as a primary procedure of choice.…”
Section: Discussionmentioning
confidence: 99%
“…However, this pressure theory has not been proven in cases of syringes associated with a Chiari I malformation and, when taken with the observation of cerebellar tonsillar descent after lumboperitoneal shunting [20, 69, 70, 71, 72, 73, 74], cannot be recommended as a primary procedure of choice.…”
Section: Discussionmentioning
confidence: 99%
“…The cerebellar tonsils usually resume a more normal position after the mass effect of hematoma has been removed. 9) Therefore, the tonsillar herniation in our patient was probably not directly associated with the supratentorial hematoma.…”
Section: Discussionmentioning
confidence: 95%
“…Mori et al thought that since the majority of Chiari malformations are congenital, the association of a Chiari I malformation, syringomyelia and GHD might be one of the midline anomaly syndromes [5]. On the other hand, Welch et al reported cases with acquired Chiari malformation, some of whom had syringomyelia as well [6]. We believe that the cases of syringomyelia without a Chiari malformation are explained by birth injury rather than by the midline anomaly syndrome, and the association of hypopituitarism with syringomylia supports the primary role of birth injury in the pathogenesis of hypopituitarism.…”
Section: Discussionmentioning
confidence: 99%